Case report: A rare secondary systemic candidiasis as a bite wound complication in a dog - Geum, Yun-Joo; Han, Hyun-Jung (Frontiers in Veterinary Science, 2024)
An 11-year-old, 4.8 kg, intact male mixed-breed dog was evaluated for a bite wound that had occurred a day prior to consultation. On examination, the patient exhibited signs of early to-late decompensatory shock, hemothorax, pneumothorax, and rib fractures. Initial shock management and resuscitation were performed. After several days of stabilization, exploratory thoracotomy, thoracic wall reconstruction, culture sampling, and antibiotic susceptibility tests were conducted. Empirical antimicrobial treatments were performed while pending culture results. Despite aggressive antimicrobial therapy, the patient had focal seizures and wound dehiscence, presumably due to the worsening of infection and inflammation. Necrotic tissues adjacent to the dehiscence were debrided, and the wound was opened. A previous analysis of wound and blood cultures identified Candida glabrata, and itraconazole was initiated in accordance with the culture results. Successful treatment was achieved, and the wound was closed. The patient remained healthy after 2 months of monitoring. To the best of our knowledge, this was the first case report of systemic candidiasis in a dog secondary to a bite wound diagnosed via blood culture. Additionally, this case highlights successful treatment with itraconazole.